Design of a New Color and Caliber Sorting Device (Texas Journal of Engineering and Technology, 2022)
The article presents the technology of creating a new modern seed sorting device for efficient use of agricultural machinery. Cotton seeds are split into pieces, mixed with kernels and husks, and then put into a press to extract oil. There are mechanical aerodynamic, fluid and electrical methods and methods of this device with low efficiency, low amount of released oil.